The Impact of Social Pensions on Intergenerational Relationships: Comparative Evidence from China - Xi Chen; Karen Eggleston; Ang Sun (Institute of Labor Economics (IZA), 2017)
China launched a new rural pension scheme (hereafter NRPS) for rural residents in 2009, now covering almost all counties with over 400 million people enrolled. This implementation of the largest social pension program in the world offers a unique setting for studying the economics of intergenerational relationships during development, given the rapidity of China's population aging, traditions of filial piety and co-residence, decreasing number of children, and dearth of formal social security, at a relatively low income level. We draw on rich household surveys from two provinces at distinct development stages impoverished Guizhou and relatively well-off Shandong to better understand heterogeneity in the impact of pension benefits. Employing a fuzzy regression discontinuity design, we find that around the pension eligibility age cut-off, the NRPS significantly reduces intergenerational co-residence, especially between elderly parents and their adults sons; promotes pensioners' healthcare service consumption; and weakens (but does not supplant) nonpecuniary and pecuniary transfers across three generations. These effects are much larger in less developed Guizhou province.
Keywords: H55; I18; J14; R28; 330; social pensions; intergenerational relationships; regional comparisons; coresidence; old-age care; service consumption; transfers